2016
DOI: 10.1212/wnl.0000000000002613
|View full text |Cite
|
Sign up to set email alerts
|

Right hemisphere structures predict poststroke speech fluency

Abstract: Objective: We sought to determine via a cross-sectional study the contribution of (1) the right hemisphere's speech-relevant white matter regions and (2) interhemispheric connectivity to speech fluency in the chronic phase of left hemisphere stroke with aphasia.Methods: Fractional anisotropy (FA) of white matter regions underlying the right middle temporal gyrus (MTG), precentral gyrus (PreCG), pars opercularis (IFGop) and triangularis (IFGtri) of the inferior frontal gyrus, and the corpus callosum (CC) was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 39 publications
(52 reference statements)
4
67
0
1
Order By: Relevance
“…Supporting our findings, in patients in the chronic state of recovery from left hemisphere ischemic stroke, FA values in specific regions of interest in the contralateral hemisphere (middle temporal gyrus, precentral gyrus, and pars opercularis) were predictive of speech fluency. 38 Similarly, in a cohort of patients with right hemispheric ischemic stroke, with the use of Tract Based Spatial Statistics, FA values in the specific regions of the contralateral hemisphere correlated with performance on neuropsychological testing. 33 Our data now offer new evidence to demonstrate the utility of global measures of WM integrity in this population.…”
Section: Resultsmentioning
confidence: 98%
“…Supporting our findings, in patients in the chronic state of recovery from left hemisphere ischemic stroke, FA values in specific regions of interest in the contralateral hemisphere (middle temporal gyrus, precentral gyrus, and pars opercularis) were predictive of speech fluency. 38 Similarly, in a cohort of patients with right hemispheric ischemic stroke, with the use of Tract Based Spatial Statistics, FA values in the specific regions of the contralateral hemisphere correlated with performance on neuropsychological testing. 33 Our data now offer new evidence to demonstrate the utility of global measures of WM integrity in this population.…”
Section: Resultsmentioning
confidence: 98%
“…Importantly, higher grey matter volume in these regions is associated with better residual language functions in chronic post-stroke aphasia patients [Xing et al, 2015]. Similarly, increased fractional anisotropy (FA) has been observed in the right IFG pars opercularis for chronic post-stroke aphasia patients relative to healthy controls, and higher FA in this region is associated with better speech production abilities for patients [Pani et al, 2016]. Our findings add to this literature by showing that functional activation in specific right frontal regions during language task performance is associated with better expressive language abilities in chronic post-stroke aphasia patients with extensive left hemispheric damage.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, higher grey matter volume in these regions is associated with better residual language functions in chronic post-stroke aphasia patients [Xing et al, 2016]. Similarly, increased fractional anisotropy (FA) has been observed in the right IFG pars opercularis for chronic post-stroke aphasia patients relative to healthy controls, and higher FA in this region is associated with better speech production abilities in patients [Pani et al, 2016].…”
Section: Right Hemispheric Compensation In Patients With Extensive Lementioning
confidence: 95%
“…2–6 One large cross-sectional study showed that aphasia severity was associated with stroke volume, time post-onset, and percentage of damage to 35 brain regions. 2 Three studies have shown a strong association between lesion load in the AF (along with the integrity of right hemisphere white matter tracts 5 ) and outcome of naming and speech fluency in post-stroke aphasia. 4–6 One longitudinal study of 21 aphasic individuals showed that age, initial severity, and the pattern of activation on functional imaging at baseline were associated with degree of impairment at six months.…”
mentioning
confidence: 99%